Chapter Polybrominated Diphenyl Ethers (PBDEs) as Emerging Environmental Pollutants: Advances in Sample Preparation and Detection Techniques - M. Nzangya, Japheth (InTechOpen, 2021)
Environmental pollution has been a challenging phenomenon in most developing countries, due to the weak enforcement of environmental regulations. As a result, humans and animals are exposed to different environmental pollutants, which threaten their very existence. Some of the emerging pollutants of great concern are polybrominated diphenyl ethers (PBDEs) since they are categorized as probable human carcinogens and are also known to bioaccumulate in fatty tissues of animals and humans, reaching toxic levels upon continued exposure. Monitoring of these pollutants is therefore paramount as it contributes to addressing the problem of human exposure and environmental pollution. Their monitoring involves sample preparation methods followed by quantification with various detection techniques. Sample preparation methods that aim at reducing matrix interferences, enriching analytes and transfer of analytes to a desirable solvent, have evolved from conventional methods to advanced methods that facilitate the detection of these chemicals at very low concentrations. Likewise, detection techniques have advanced from chromatographic detection techniques to miniaturized systems that involve sensors. This chapter discusses PBDEs as emerging pollutants, their sources, and toxicological implications on humans, as well as advances in sample preparation methods and detection techniques in the determination of PBDEs.